Assessing the Dynamic Economic Impact of Tourism in a Developing Region in South Africa - C., De Bruyn; N., Meyer; D.F., Meyer (Journal of Economics and Behavioral Studies, 2018)
According to the National Development Plan (NDP), the three main developmental problems South Africa is facing include: high levels of unemployment, poverty and inequality. Tourism, as an economic sector, has been cited as a possible solution to create much-needed employment and income which could lead to reduced poverty and improved inequality. Tourism could be used in developing regions as a driver of economic growth. The objective of this study is to determine the dynamic impact of the tourism sector on economic growth in a developing region in South Africa, namely the Vaal-Triangle region. The research methodology followed a quantitative design, using a pooled panel approach including the two municipal areas of Metsimaholo and Emfuleni which comprises the Vaal region. Annual data from 2001 to 2017 were used to analyse the impact of growth in tourism on economic growth. Economic growth was set as the dependent variable and tourism measurements such as tourism spending and trips as the independent variables. Results from the analysis confirm the original hypothesis that tourism growth has a significant impact on economic growth. The sector therefore, has the potential to create employment opportunities and alleviate poverty in a developing region if promoted and supported to its full potential.